Analysis of Arrhythmia of the Heart in Dogs - Ankush Rana; Pardeep Sharma; Deepti Bodh; Ankur Sharma; Ajay Katoch; Adarsh Kumar (The Indian Veterinary Journal, 2025)
The incidence of cardiac arrhythmias was studied in 435 dogs with a history of generalized diseases over a period of one year and two months from July 2022 to September 2023. The assessment was aimed to evaluate arrhythmias incidences and revealed 114 dogs (26.21%) exhibited various types, such as atrial fibrillation (30.70%), ST- coving and sinus arrest (9.65%, each), and ST-segment elevation (8.77%, each). Notably, atrial fibrillation had the highest incidence. Dogs over six years old accounted for most cases (59.64%), and Labradors showed the highest breed-specific occurrence (29.82%). Male dogs were more prone to arrhythmias (81.58%) than females (18.42%). This comprehensive analysis sheds light on the incidence and characteristics of arrhythmias in dogs.